Factors affecting affect cardiovascular health in Indonesian HIV patients beginning ART - Karim, B.; Wijaya, I.; Rahmaniyah, R.; Ariyanto, I.; Waters, S.; Estiasari, R.; Price, Patricia (2017)
Background: We present a small longitudinal study of how demographic factors and persistent burdens of HIV and cytomegalovirus (CMV) influence cardiovascular health in young adults beginning ART in an inner-city clinic in Jakarta, Indonesia. Methods: ART-naïve HIV patients [n = 67; aged 31 (19 to 48) years] were enrolled in the JakCCANDO Project. Echocardiography and carotid Doppler ultrasonography were performed before ART (V0) and after 3, 6, and 12 months (V3-12). Antibodies reactive with CMV lysate or IE-1 protein were assessed at each timepoint and CMV DNA was identified at V0. Results: Markers of adverse cardiovascular prognosis [left ventricular mass index, ejection fraction and carotid intimal media thickness (cIMT)] were similar to healthy controls, but increased at V12. Internal diameters of the carotid arteries and systolic blood pressure correlated with HIV disease severity at V0, but cardiac parameters and cIMT did not. E/A ratios (left ventricular diastolic function) were lower in patients with CMV DNA at V0, but this effect waned by V6. Levels of antibody reactive with CMV IE-1 correlated inversely with CD4 T cell counts at V0, and levels at V6-V12 correlated directly with the right cIMT. Conclusions: Overall the severity of HIV disease and the response to ART have only subtle effects on cardiovascular health in this young Asian population. CMV replication before ART may have a transient effect on cardiac health, whilst antibody reactive with CMV IE-1 may mark a high persistent CMV burden with cumulative effects on the carotid artery.